Protein engineering for covalent immobilization and enhanced stability through incorporation of multiple noncanonical amino acids - Deepankumar, Kanagavel (2017)
In this study, we demonstrate the application of multiple functional properties of proteins generated through coupling of residue-specific and site-specific incorporation method. With green fluorescent protein (GFP) as a model protein, we constructed multifunctional GFP through sitespecific incorporation of L-3,4-dihydroxyphenylalanine (DOPA) and residue-specific incorporation of (2S, 4S)-4- fluoroproline (4S-FP) or L-homopropargylglycine (hpg). Fluorescence analysis revealed a conjugation efficiency of approximately 20% for conjugation of DOPA-containing variants GFPdopa, GFPdp[4S-FP], and GFPdphpg onto chitosan. While incorporation of 4S-FP improved protein folding and stability, hpg incorporation into GFP allowed conjugation with fluorescent dye/polyethylene glycol (PEG). In addition, the modification of GFPhpg and GFPdphpg with PEG through Cu(I)-catalyzed click reaction increased protein thermal stability by about two-fold of the wild-type GFP.